VENOUS THROMBOSIS - Akmal A. Irnazarov; Vali R. Khasanov; Ilhom R. Beknazarov; Rustambek A. Karimov; Dinara Kh. Irnazarova (Central Asian Journal of Medicine, 2023)
This paper describes the distribution and complications of venous thrombosis of deep veins of the lower extremities. It is emphasized that the main method of treatment for this pathology is surgical, namely endovascular. Endovascular treatment methods significantly reduce the risk of pulmonary embolism and the development of post-thrombophlebitic syndrome.